Profiling of Dominant Bacteria in Traditional Buffalo Milk Cheese “Dangke” Based on 16S rRNA Sequencing - Mutmainna, A.; Arief, I. I.; Budiman, C.; Abidin, Z.; Wulandari, Z. (Tropical Animal Science Journal, 2025)
Metagenomic approaches are highly valuable in food microbiology, particularly for the investigation of traditional fermented products such as dangke buffalo milk cheese from South Sulawesi, Indonesia. Buffalo milk, a primary raw material, contains diverse biochemical and bioactive components that are produced by microbial activity during fermentation. Unlike conventional culture-based techniques, metagenomics enables the comprehensive characterization of microbial communities directly from food matrices. This study aimed to identify the key microbial taxa that contribute to the dangke quality of fermentation and to understand the factors influencing it. Bacterial 16S rRNA genes were amplified using primers 27F and 1492R under optimized polymerase chain reaction conditions. DNA concentrations were measured with NanoDrop and Qubit instruments, and sequencing was conducted using Oxford Nanopore Technology with MinKNOW software (v23.04.5). Metagenomic analysis revealed Enterococcus faecium as the dominant lactic acid bacterium across all dangke samples (P1–P3), emphasizing its crucial role in fermentation and probiotic potential. These findings suggest that E. faecium can enhance the quality and functional properties of dangke. Moreover, metagenomic tools can support the development of standardized fermentation practices and microbial safety assessments for traditional dairy products.